Evaluating engineered networks: the effects of structure and process on the outcome of the Brazilian small-firm networks. (2019) - Bortolaso, Ingridi; Verschoore, Jorge Renato; Rigoni, Eduardo Henrique
This paper focuses on the evaluation of engineered networks created and supported by a public policy, namely cooperation networks program (CNP), guided by the Government of Rio Grande do Sul State, in Brazil. Since the year 2000, the CNP fostered the establishment of more than 200 SFNs in the region, turning this state into the main empirical field of studies on interorganisational networks in Brazil. This context raises questions regarding the SFNs genesis and its consequences. The paper, thus, seeks to answer the following question: can it be affirmed that structure and process influence the Brazilian engineered SFNs outcome? To do so, a quantitative research was conducted with the CNP networks based on the categories structure, process, and outcome. The results indicate that through an adequate network evaluation, it is possible to measure and compare results, besides facilitate intervention decisions for course corrections and obtain the targeted collective gains.